2011
DOI: 10.1093/toxsci/kfr280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Hexavalent Chromium in the Alimentary Canal of F344 Rats and B6C3F1 Mice Following Exposure in Drinking Water: Implications for Carcinogenic Modes of Action

Abstract: Exposure to high concentrations of hexavalent chromium (Cr[VI]) in drinking water is reported to induce oral mucosa tumors in F344 rats and intestinal tumors in B6C3F1 mice. To investigate the modes of action underlying these tumors, 90-day drinking water studies (with interim necropsy at day 8) were conducted with concentrations of 0.1–182 mg/l Cr(VI), administered as 0.3–520 mg/l sodium dichromate dihydrate. Blood and tissue samples were analyzed for chromium content, oxidative stress, iron levels, and gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(94 citation statements)
references
References 29 publications
8
84
2
Order By: Relevance
“…Although there was no neoplastic effect observed in this study due to the short duration of exposure, analysis of this study provided insights into potential mechanisms underlying Cr(VI)-induced tumor formation. First, the ratio of reduced-to-oxidized glutathione (GSH/GSSG), which is an indicator of oxidative stress, was decreased in both rats [57] and mice [46], suggesting Cr(VI) exposure caused oxidative stress in both species and also indicating that a substantial portion of Cr(VI) was not reduced in the GI tract.. While total Cr levels were comparable in the rat and mouse, the reduced GSH/GSSG ratio was only observed in rat oral mucosae and mouse duodenum, the sites that formed tumors in the NTP 2-yr study [46,57].…”
Section: Mechanisms Of Chromium Toxicity and Carcinogenicitymentioning
confidence: 99%
“…Although there was no neoplastic effect observed in this study due to the short duration of exposure, analysis of this study provided insights into potential mechanisms underlying Cr(VI)-induced tumor formation. First, the ratio of reduced-to-oxidized glutathione (GSH/GSSG), which is an indicator of oxidative stress, was decreased in both rats [57] and mice [46], suggesting Cr(VI) exposure caused oxidative stress in both species and also indicating that a substantial portion of Cr(VI) was not reduced in the GI tract.. While total Cr levels were comparable in the rat and mouse, the reduced GSH/GSSG ratio was only observed in rat oral mucosae and mouse duodenum, the sites that formed tumors in the NTP 2-yr study [46,57].…”
Section: Mechanisms Of Chromium Toxicity and Carcinogenicitymentioning
confidence: 99%
“…Therefore, adverse systemic effects of Cr(VI) are potentially due to (1) direct effects of Cr(VI) in the blood, or (2) secondary effects such as changes in blood redox or iron homeostasis. Exposure to Cr(VI) was shown previously to alter serum GSH/GSSG levels and ratios (Thompson, Proctor, et al, 2011; Thompson et al, 2012), as well as induce iron depletion (Suh et al, 2014). Because the Cr(VI) PBPK model (Kirman et al, 2017) can estimate the amount of Cr(VI) entering (i.e., fluxing) into the portal circulation from the gastrointestinal tract, this dose metric was used for effects of Cr(VI) manifested beyond the intestinal mucosa, whether by direct or indirect mechanisms.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, we previously observed dose‐dependent decreases in the reduced/oxidized glutathione (GSH/GSSG) ratio (i.e., increased oxidation) in oral samples in F344 rats but not mice (Thompson et al, 2012). However, given the lack of gene expression changes in the oral mucosa (Thompson et al, 2016), the change in GSH/GSSG ratio may not have occurred in the oral mucosa tissue per se, but rather in the saliva or microbiota present in the oral cavity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies showed relatively increased levels of chromium VI in the liver, kidney, and spleen, while RBC and plasma chromium levels were only modestly elevated after exposure to chromium VI (Costa, 1997;Thomann et al, 1994;Witmer et al, 1989;Collins et al, 2011;Witt et al, 2013). Thompson et al (2011Thompson et al ( , 2012 reported significant increases in total chromium concentrations in the oral cavity, glandular stomach, duodenum, jejunum, and ileum of rats and mice following 90 days of exposure to sodium dichromate dihydrate in drinking water. The half-life of chromium in various tissues of rats who are administered chromium VI was long and exceeded 20 days.…”
Section: Occurrence Sources and Use Of Chromium Compoundsmentioning
confidence: 99%